Strong Monotonicity in Surplus Sharing - Eric Friedman (Rutgers University, Department of Economics, 1999)
We consider three new axioms for surplus sharing problems. The first is strong monotonicity which says that workers should be rewarded for increases in productivity and the second says that productive workers should receive some compensation. The third requires that the surplus sharing rule should be well defined (and continuous on) the set of threshold functions. We show that none of the standard ``equitable'' mechanisms satisfy either of these axioms and then present a constructive characterization of mechanisms which do. Using this we construct several new mechanisms. These are the Almost Flat mechanism, the Spread Aumann-Shapley mechanism, and the Spread Serial mechanism, which have many desirable properties.
Keywords: 330; cost allocation